Labelling Study of Sodium Citrate With Tc99m and The Bological Behaviour Of The Labelled Complex as Kidney Functioal Agent - Khalida, S. M (College of Pharmacy / Mustansiriyah University, 2013)
The objective of this study is to optimize the parameters for the development of a procedure for preparing Sn-sodium citrate label with Tc99m, of providing a stable complex after mixing with Tc99m-pertechnetate and to find the potential of technetium- 99m (Tc99m) citrate complex as a new kidney functional agent. The labeling conditions of Tc99m citrate complex using stannous chloride dehydrate as a reducing agent for pertechnetate have been described. The gel chromatography scanning (GCS) method reveals that the labeling efficiency of Tc99m-citrate complex is promoted by raising the pH of the preparation to (pH=4) using 1N NaOH. The optimal amounts of the reactants in the preparation to obtain labeled and stable complex with high kidney uptake were found to be (1mg) sodium citrate and (100 μg) SnCl2.2H2O. The results show that high labeling yield (≥95%) for the labeled complex. The data of bio distribution experiments in the laboratory animals (mice), clear high radioactivity accumulation of labeled complex in kidney at 5 minutes post injection. The results of bio distribution of labeled complex have shown a good biological behavior with low radioactivity accumulation in the non-target organs (blood, liver and other organs).